1999
DOI: 10.1002/(sici)1097-4636(199907)46:1<44::aid-jbm5>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of bioprosthetic heart valve failure: Fatigue causes collagen denaturation and glycosaminoglycan loss

Abstract: Bioprosthetic heart valve (BPHV) degeneration, characterized by extracellular matrix deterioration, remodeling, and calcification, is an important clinical problem accounting for thousands of surgeries annually. Here we report for the first time, in a series of in vitro accelerated fatigue studies (5-500 million cycles) with glutaraldehyde fixed porcine aortic valve bioprostheses, that the mechanical function of cardiac valve cusps caused progressive damage to the molecular structure of type I collagen as asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 0 publications
4
59
0
1
Order By: Relevance
“…It is well known, that the GAG content and type have a significant role in the mechanical performance of tissues such as bovine pericardium [21,36,38] and porcine heart valves [39]. In this study, we observed a reduction in GAG content on bovine pericardial tissue and therefore it was expected that the tensile properties would be affected to different extents depending on the amount of GAG removed.…”
Section: Discussionmentioning
confidence: 57%
“…It is well known, that the GAG content and type have a significant role in the mechanical performance of tissues such as bovine pericardium [21,36,38] and porcine heart valves [39]. In this study, we observed a reduction in GAG content on bovine pericardial tissue and therefore it was expected that the tensile properties would be affected to different extents depending on the amount of GAG removed.…”
Section: Discussionmentioning
confidence: 57%
“…Scaffolding material eventually disappears leaving only the necessary healthy tissue in a topologically required form. 8,9,11 The 3D matrix provides more space for cellular colonization and proliferation as well as provides a different set of physiological signals to the developing tissue. One option for creating tissue scaffolds is to use extracellular matrix (ECM) components derived from animal sources.…”
Section: Basics Of Porous Structuresmentioning
confidence: 99%
“…The electrophysiologic parameters of pigs also more closely resemble those of man than other models, except the non-human primate (Liedtke et al, 1975;Bowman and Hughes, 1984;Hughes, 1986). Moreover, cardiovascular surgical procedures using swine have been technically feasible for ventricular assist devices for patients suffering from acute myocardial infarction (Vyavahare et al, 1999;Schoen and Levy, 2009), vascular stents, and restenosis (David et al, 1998;David et al, 2009), which make swine a unique surgical model.…”
Section: Swinementioning
confidence: 99%